Side Plank Pose Exercises for Adolescent Idiopathic Scoliosis Patients—Some Concerns About a Randomized Controlled Trial - Loren M Fishman MD, BPhil (Oxon.) (Global Advances in Health and Medicine, 2021)
In their recent article, Side Plank Pose Exercises for Adolescent Idiopathic Scoliosis Patients, Sarkisova, et. al. found no beneficial effect using the simple poses that Drs. Groessl, Sherman and I found successful in reversing adolescent idiopathic scoliosis (AIS) and degenerative scoliosis (DS). Although they tried to follow our protocol exactly, they did not. They did not distinguish thoracic from lumbar or thoracolumbar from complex (both thoracic and lumbar) curves, affecting the randomization. See Figure 2 in their study. The side plank is only intended to reverse lumbar and thoracolumbar curves, and actually exaggerates thoracic curves, and the thoracic component of complex curves. The vicissitudes of randomization placed 25 lumbar and thoracolumbar curves in the control and non-compliant groups, but no lumbar and only one thoracolumbar in the intervention group that did the side plank. This trial did not prove that the side plank does not reduce lumbar curves: none were tested.